Laboratory and field screening of allopathic potential bread wheat (Triticum aestivum L.) varieties in Bangladesh: Screening the Allelopathic Potential of Bread Wheat Varieties in Bangladesh - Shohan, M T A; Ali, M H; Hasanuzzaman, M; Malek, M; Masum, S M (Bangladesh Journal of Agriculture, 2025)
Minimizing the use of herbicides for eco-friendly weed management in wheat (Triticum aestivum L.) has become increasingly necessary. A series of experiments were conducted to screen the potential allelopathic wheat varieties of Bangladesh. In the laboratory these studies used radish (Raphanus sativus L.) and lettuce (Lactuca sativa L.) as model receiver plants, along with lambsquaters (Chenopodium album L.), and slender amaranth (Amaranthus viridis L.) as test weeds, for the initial allelopathic activity screenings of 13 wheat varieties of Bangladesh. In the laboratory studies, the wheat var. BARI gom21 produced the highest inhibition effect on C. album roots and also reduced the speed of germination of seeds of R. sativus, L. sativa, C. album, and A. viridis. BARI gom21 also significantly affected the coefficient of the velocity of germination of A. viridis. The focus of field studies was on 11 wheat varieties, which had previously been screened in the laboratory. These eleven wheat varieties were selected and cultivated in the field using standard cultural practices, but with no additional weed control. The field studies showed that wheat var. BARI gom21 had the lowest weed infestation with maximum weed control efficiency. In addition, the var. BARI gom21 were free of many weed species, including C. album and A. viridis. Therefore, BARI gom21 was the most weed suppressive variety among the tested varieties. Bangladesh J. Agri. 2025, 50(1): 83-94